Phytochemical Analysis, Antioxidant and Antibacterial Activity of Robusta Coffee (Coffea canephora) Extract From West Lampung - Iffa Afiqa Khairani; Hida Arliani Nur Anisa; Jeane Siswitasari Mulyana; Elisa Nurma Riana; Wahyuni Dian Lestari (Elkawnie, 2025)
Abstract: Robusta coffee (Coffea canephora) is one of Indonesia's export commodities, which is widely grown in Lampung Province. West Lampung Regency is the main producer of robusta coffee in Lampung Province. Robusta coffee contains various metabolites with potential as an antioxidant and antibacterial properties. This study aims to analyze the metabolite content (phytochemical compounds) of robusta coffee ethanol extract qualitatively and quantitatively, followed by determining antioxidant activity (DPPH method) and antibacterial activity (MIC and MBC method) against tested bacteria including Bacillus subtilis ATCC 6633, Eschericia coli ATCC 8739, Pseudomonas aeruginosa ATCC 9027, and Staphylococcus aureus ATCC 25923. Robusta coffee extract from West Lampung showed positive results for phytochemical compounds such as phenolic compounds, flavonoids, tannins, saponins, terpenoids, alkaloids, and negative for steroids. The quantification results of total phenolic content (TPC) were 62.88 mgGAE/g extract, total flavonoids content (TFC) were 23.90 mgQE/g extract, total tannins content (TTC) were 176.73 mgTAE/g extract, and total saponins content (TSC) were 10.37%. This extract classified as a very strong antioxidant with an IC50 value of 35.02 ppm, and moderate antibacterial activity at a concentration of MIC/MBC 125/125 ppm against all bacterial tested. Therefore, robusta coffee extract was a natural ingredient with potential antioxidant and antibacterial properties. Abstrak: Kopi robusta (Coffea canephora) merupakan salah satu komoditas ekspor Indonesia yang banyak ditanam di Provinsi Lampung. Kabupaten Lampung Barat merupakan penghasil utama kopi robusta di Provinsi Lampung. Kopi robusta mengandung berbagai metabolit yang berpotensi sebagai antioksidan dan antibakteri. Penelitian ini bertujuan untuk menganalisis kandungan metabolit (senyawa fitokimia) dari ekstrak etanol kopi robusta secara kualitatif dan kuantitatif, dilanjutkan dengan pengukuran aktivitas antioksidan (metode DPPH) dan aktivitas antibakteri (metode MIC dan MBC) terhadap bakteri uji yang meliputi Bacillus subtilis ATCC 6633, Eschericia coli ATCC 8739, Pseudomonas aeruginosa ATCC 9027, dan Staphylococcus aureus ATCC 25923. Ekstrak kopi robusta dari Lampung Barat positif mengandung senyawa fitokimia seperti senyawa fenolik, flavonoid, tanin, saponin, terpenoid, alkaloid, dan negatif steroid. Hasil kuantifikasi kandungan fenolik total (TPC) sebesar 62,88 mgGAE/g ekstrak, kandungan flavonoid total (TFC) sebesar 23,90 mgQE/g ekstrak, kandungan tanin total (TTC) sebesar 176,73 mgTAE/g ekstrak, dan kandungan saponin total (TSC) sebesar 10,37%. Ekstrak ini tergolong antioksidan yang sangat kuat dengan nilai IC50 sebesar 35,02 ppm, dan aktivitas antibakteri sedang pada konsentrasi MIC/MBC 125/125 ppm terhadap seluruh bakteri uji. Dengan demikian, ekstrak kopi robusta merupakan bahan alami yang memiliki potensi sebagai antioksidan dan antibakteri.